RAISING THE AWARENESS OF HALAL PRODUCTS AMONG INDONESIAN CONSUMERS: ISSUES AND STRATEGIES - Tengku Harunur Rasyid (Indonesian Journal of Agricultural Economics, 2010)
The bargaining power of consumers is a significant factor that determines the structure ofindustry competition. Due to the fact that the majority of Indonesians are Muslim, issues on nonhalal products have significant impact on processed food business. In regards to this increasedawareness in the community, there are some problems related to processed food businesses,which are consumers’ perceptions, producers’ concerns, limited number of accreditationinstitution ofice, and costly procedures of halal certification. Analysis of this issues used SoftSystem Methodology (SSM), where the transformation processes expected was set up, scenarioswere built and strategies in raising halal awareness were developed based on scenarios. Theconclusion is that the government should be able to evaluate the impact and immediacy of theissues, and developing appropriate strategies to establish a favorable business environment aswell as satisfy community’s needs. The successful of this strategy definitely is unable to get bywithout the government’s seriousness in performing its function as public servant andgovernment’ political will to protect the communi t y f rom publi c decept ion acti ons.